1990
DOI: 10.1042/cs0780445
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor accelerates functional recovery from ischaemic acute tubular necrosis in the rat: Role of the epidermal growth factor receptor

Abstract: 1. Severe, ischaemic, acute tubular necrosis was induced in rats by bilateral occlusion of the renal arteries. The experimental group received exogenous epidermal growth factor infused directly into the renal arterial circulation. Serum creatinine concentration was measured daily for 1 week. Epidermal growth factor receptor binding was measured by autoradiography of whole kidney sections. Renal cell proliferation was measured by incorporation of [3H]thymidine into DNA. 2. Serum creatinine concentration increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 0 publications
2
73
0
Order By: Relevance
“…They suggest that these changes could be a consequence of kidney damage and may reflect the events leading to renal failure or alternatively, and that reduced EGF synthesis is an adaptation permitting restoration ofkidney function (26). Support for the former hypothesis is provided by Humes et al (27) and Norman et al (28) who showed that administration of EGF to rats enhances renal tubule cell regeneration and repair and accelerates the recovery of renal function in postischemic acute renal failure. In view of the action of EGF to enhance IGF I gene expression in collecting duct, it is possible that production of endogenous EGF provides a stimulus for IGF I expression during ischemic renal injury.…”
Section: Discussionmentioning
confidence: 48%
“…They suggest that these changes could be a consequence of kidney damage and may reflect the events leading to renal failure or alternatively, and that reduced EGF synthesis is an adaptation permitting restoration ofkidney function (26). Support for the former hypothesis is provided by Humes et al (27) and Norman et al (28) who showed that administration of EGF to rats enhances renal tubule cell regeneration and repair and accelerates the recovery of renal function in postischemic acute renal failure. In view of the action of EGF to enhance IGF I gene expression in collecting duct, it is possible that production of endogenous EGF provides a stimulus for IGF I expression during ischemic renal injury.…”
Section: Discussionmentioning
confidence: 48%
“…Infusion ofadenine nucleotides or EGF can speed recovery of injured kidney tubules in rats with experimental acute renal failure (7,(54)(55)(56). The results indicated that EGF was as potent as adenosine and adenine nucleotides, basic FGF and IGF-I were much less stimulatory, and PDGF, IGF-II, and acidic FGF had no effect.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, the renal growth that follows unilateral nephrectomy is associated with increased renal EGF [11,10] and the associated tubular cell hyperplasia can be reduced by the administration of anti-EGF antibodies [28]. In acute tubular necrosis following ischaemic injury [29,30] or mercuric chloride toxicity exogenously administered EGF accelerates tubular regeneration and recovery. The factors responsible for increased EGF during early diabetes remain speculative.…”
Section: Discussionmentioning
confidence: 99%